Faktor-Faktor yang Mempengaruhi Wanita Usia Subur (WUS) dalam Pemeriksaan Pap Smear di Puskesmas Kotabaru Kecamatan Keritang Kabupaten Indragiri Hilir Riau Tahun 2023 - Hikmah, Andi; Monica, Olivia Tri; Ningsih, Nisa Kartika (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the factors that influence women of childbearing age in having Pap Smear examinations at the Kotabaru Community Health Center, Keritang District, Indragiri Hilir Regency, Riau in 2023. This research method is analytical research, with a cross-sectional approach with a sample size of 60 respondents, using data namely primary data (questionnaire), analysis using Chi Square. The results of the research show that there is a significant relationship between the variables age, employment and husband's support with the Pap Smear examination, while the variables that are not related to the Pap Smear examination are parity, education and knowledge at the Kotabaru Health Center, Keritang District, Indragiri Hilir Regency, Riau in 2023